(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Diabetes mellitus is a serious metabolic disease that is characterized by high blood sugar levels resulting from absolute or relative insufficient insulin secretion and action which in turn causes micro and macro-vascular complications. Even though Metformin hydrochloride is regarded as the drug of first choice, its frequent dosage and adverse gastrointestinal effects may affect compliance. Herbal drugs like Cissus quadrangularis have anti-diabetic, antioxidant, anti-inflammatory, and anti-hyperlipidemic effects. This study, therefore, aimed to design, formulate and evaluate Herbo-allopathic bilayer tablet with immediate release of Metformin and sustained release of Cissus extract for the treatment of type 2 diabetes mellitus. The stems of C. quadrangularis were extracted using appropriate solvents. Preliminary phytochemical screening, physicochemical and spectroscopic studies were conducted. Drug-excipient compatibility was also assessed. Metformin immediate release and Cissus sustained release were achieved by direct compression method using appropriate excipients. Pre-compression and post-compression parameters were evaluated. Dissolution test was performed using USP dissolution apparatus II and results compared with those of the marketed products. Accelerated stability studies were also carried out. This study showed that the bilayer tablet formulation of Metformin HCl and Cissus extract had desirable physicochemical properties and drug release characteristics. It was therefore concluded that the combination of herbal drug and allopathic drug would contribute to better management of type 2 diabetes mellitus with minimal occurrence of adverse effects and improved patient compliance due to reduced dosing frequency.